2021
DOI: 10.1145/3462448
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking Non-Dualistic Design: The Soma Design Case

Abstract: We report on a somaesthetic design workshop and the subsequent analytical work aiming to demystify what is entailed in a non-dualistic design stance on embodied interaction and why a first-person engagement is crucial to its unfoldings. However, as we will uncover through a detailed account of our process, these first-person engagements are deeply entangled with second- and third-person perspectives, sometimes even overlapping. The analysis furthermore reveals some strategies for bridging the body-mind divide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…The three case studies strongly highlight the first-person perspective of the performer (a combined role of the musician and the mover) and emphasize incorporating the performer into the design process as a cocreator. Drawing from soma design and embodied music interaction, we employ three tactics: (a) defamiliarization, (b) extending musical movement vocabulary, and (c) creative artifacts (Van Der Schyff et al, 2018 ; Höök et al, 2021 ).…”
Section: Design Approach and Methodologymentioning
confidence: 99%
“…The three case studies strongly highlight the first-person perspective of the performer (a combined role of the musician and the mover) and emphasize incorporating the performer into the design process as a cocreator. Drawing from soma design and embodied music interaction, we employ three tactics: (a) defamiliarization, (b) extending musical movement vocabulary, and (c) creative artifacts (Van Der Schyff et al, 2018 ; Höök et al, 2021 ).…”
Section: Design Approach and Methodologymentioning
confidence: 99%
“…It fosters community interaction, well-being, and a sense of belonging within the built environment. SOMA Design practices include "designing with and through kinesthetic experience" aiming at bridging the body-mind dichotomy "by attending to our inner universe and dissolving or traversing dichotomies between inside and outside [...] body and technology" (Höök et al, 2021). In the case study we developed, we could observe an entangled relationship (Frauenberger, 2019) between Eleonora and the technology.…”
Section: Inclusivity and Embodiementmentioning
confidence: 99%
“…Current research has shown that expressive interfaces that represent biosignals/emotion data that enable the exploration and engagement with biodata help mindful self-awareness, self-reflection and regulation of affect states, empathy, compassion and caregiving, relationship skills for authentic social connection, motivation, performance, and coordinative effort [18,24]. Expressive biodata interfaces are increasingly used also for the design of and research on somaesthetic experiences (e.g., the Breathing Light in [7,8], Breeze around your neck in [1], BrightHearts in [7,11], Balance Beam in [6]). Current research in soma-based design shows that such interactive material representations of soma (the felt-self) [5] enable not only the deepening of the awareness of one's soma but also the discovery of novel interactions with soma and help to understand the bodily engagement in somatic experiences [1].…”
Section: Related Workmentioning
confidence: 99%